Pemanfaatan Media Sosial Instagram @Sahabat_umkm: Studi Uses and Gratification Sebagai Upaya Edukasi Pelaku Usaha Mikro - Pratama, Muhammad Tarel Rizky; Pamungkas, Indra Novianto Adibayu; Pramesthi, Jasmine Alya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Digitalization is increasingly advancing, and one manifestation of this progress is the emergence of the social media platform Instagram. Micro-business owners utilize Instagram to meet their needs (uses and gratification), particularly in seeking education for micro-business ventures. One of the accounts disseminating education for micro-businesses is @sahabat_umkm. The objective of this research is to measure the extent of the influence of utilizing Instagram @sahabat_umkm: a study on uses and gratification as an effort in educating micro-business owners. The research method employed is causal quantitative. Data analysis techniques include Pearson product-moment correlation analysis, t-test, simple linear regression analysis, and coefficient of determination test. The data was collected by the researcher online using a questionnaire and distributed to 399 respondents who are followers of Instagram @sahabat_umkm. The sampling technique used by the researcher is Nonprobability Sampling, specifically Purposive Sampling. The result of the Pearson product-moment correlation analysis is 0.472, indicating a moderate to strong relationship between the variables of Instagram utilization and the effort in educating micro-business owners. Additionally, the magnitude of the influence on the variable of Instagram @sahabat_umkm utilization on the variable of effort to educate micro-business owners is 22.2%, while 72.8% is influenced by other factors beyond this study. The results of the simple linear regression analysis indicate that every one-unit increase in the Instagram @sahabat_umkm utilization variable corresponds to an increase of 0.231 in the variable of effort to educate micro-business owners. Through this research, it is proven that the utilization of Instagram @sahabat_umkm (variable X) significantly and positively impacts the effort to educate micro-business owners (variable Y).